Management of septic shock: a protocol-less approach - Cabrera, Jorge L. (Crit Care, 2015)
CITATION: ProCESS Investigators, Yealy DM, Kellum JA, Huang DT, Barnato AE, Weissfeld LA, Pike F, Terndrup T, Wang HE, Hou PC, LoVecchio F, Filbin MR, Shapiro NI, Angus DC. A randomized trial of protocol-based care for early septic shock. N Engl J Med. 2014; 370:1683–93. BACKGROUND: In a single-center study published more than a decade ago involving patients presenting to the emergency department with severe sepsis and septic shock, mortality was markedly lower among those who were treated according to a 6-h protocol of early goal-directed therapy (EGDT), in which intravenous fluids, vasopressors, inotropes, and blood transfusions were adjusted to reach central hemodynamic targets including central venous pressure, central venous oxygen saturation, and indirect estimates of cardiac output, than among those receiving usual care. METHODS: Objective: The objective was to determine whether these EGDT findings were generalizable and whether all aspects of the EGDT protocol were necessary to achieve those outcomes. Design: A multicenter randomized three-arm controlled trial. Setting: Thirty-one academic emergency departments in the United States. Subjects: Patients older than 18 years of age presenting to the emergency department with septic shock. Intervention: Patients were assigned to one of three groups for 6 h of resuscitation: protocol-based EGDT as defined by River and colleagues; protocol-based standard therapy that did not require the placement of a central venous catheter, administration of inotropes, or blood transfusions; and usual care which mandated no specific monitoring or management approaches. Outcomes: The primary end point was 60-day in-hospital mortality. Also tested sequentially was whether protocol-based care (EGDT and standard therapy groups combined) was superior to usual care and whether protocol-based EGDT was superior to protocol-based standard therapy. Secondary outcomes included longer-term mortality and the need for organ support. RESULTS: A total of 1,351 patients were enrolled, of whom 1,341 were evaluable due to patient/family request: 439 were randomly assigned to protocol-based EGDT, 446 to protocol-based standard therapy, and 456 to usual care. Resuscitation strategies differed significantly with respect to the monitoring of central venous pressure and central venous oxygen and the use of intravenous fluids, vasopressors, inotropes, and blood transfusions. By 60 days, there were 92 deaths in the protocol-based EGDT group (21.0 %), 81 in the protocol-based standard therapy group (18.2 %), and 86 in the usual care group (18.9 %) (relative risk with protocol-based therapy versus usual care, 1.04; 95 % confidence interval, 0.82 to 1.31; P = 0.83; relative risk with protocol-based EGDT versus protocol-based standard therapy, 1.15; 95 % CI, 0.88 to 1.51; P = 0.31). There were no significant differences in 90-day mortality, 1-year mortality, or the need for organ support. CONCLUSIONS: In a multicenter trial conducted in the tertiary care setting, protocol-based resuscitation of patients in whom septic shock was diagnosed in the emergency department did not improve outcomes.